Geological modeling and upscaling of the Ronier 4 block in Bongor basin, Chad - Mahamat Tahir Abdramane Mahamat Zene; Nurul Hasan; Jiang Ruizhong; Guan Zhenliang; Christ Trang (Journal of Petroleum Exploration and Production Technology, 2019)
Abstract The study focuses on building a 3D-dimensional model for using well log data of 3 wells to enable a better understanding of the reservoir characteristics and evaluation of the hydrocarbon potential in the field of Ronier in the Bongor Basin, Chad. These data are used to build a Lithofacies model, property model, the permeability model and the saturation model which are the parameters that describe the reservoir. Indeed, the accuracy to quantify the geological reserve of Ronier 4 reservoir block depends on the estimation of these values. The result of geological modeling and upscaling of the Ronier 4 block of Ronier oilfield is presented systematically. In this work, a Sequential Gaussian Simulation (SGS) algorithm under the phase control based on the collocated co-Kriging is adopted and the models of porosity, permeability and saturation are established. Lithofacies model has sand (0) content of 66.69% mostly the first layer, while the code (2) shale content 12.15% mostly concentrated in the center, north and south. Finally, the code (3) sand content is 21.16%. The NTG distribution is highly concentrated in the north, center and south (1) and 0.7 on average, while the lowest range is 0.1. The study shows a good permeability range between 460 to 1200 and 500 mD on average. The porosity distribution mainly distributed between 17 to 27 and 19% on average. These indicate that it has good reservoir properties. The 3D developed geological model provides the basis for calculating the Oil Initially in Place (OIIP) volumes of hydrocarbons.